Innovation platforms for better breeds for better dairying - International Livestock Research Institute (International Livestock Research Institute, 2016)
A film on how ILRI's Dairy Genetics East Africa project uses innovation platforms to improve knowledge sharing between dairy sector players to improve dairy cow breeds.